Efficient bit rate control method for distributed video coding system - Lee, Chang Woo (EURASIP journal on advances in signal processing, 2012)
An efficient bit rate control method for the transform domain distributed video coding (DVC) system is proposed. In order to decide quantization levels of each transform coefficient in the proposed distributed video decoder, a new bitplanewise zigzag scanning method is used. The bit rate can be controlled precisely in the proposed system, since the number of available bit rates is equal to the number of bitplanes. On the other hand, the bit rate is controlled by changing fixed quantization tables in conventional methods. In the proposed DVC system, Wyner-Ziv frames can be efficiently reconstructed by refining the side information with transmitted parity bits. If there is no transmitted parity bit, the side information is not refined and it is considered to be a decoded Wyner-Ziv frame. The side information is refined more precisely, as the amount of transmitted parity bits increases. The proposed DVC system provides superior coding performance with a precise bit rate control compared to conventional methods.